Pengendalian Kekerasan Seksual Terhadap Anak di Kabupaten Karawang - Nurdiansyah, Fiqri Fadilah; Kurniati, Grasia (Peneliti.net, 2024)
With the Covid-19 pandemic, many companies are related to government regulations and health reasons to carry out work from home activities, as well as resulting in workers being laid off, this policy has an impact on providing remuneration for workers. This is the background to the problem of how legal protection for laid-off workers is remuneration during the Covid-19 pandemic stems from the prevailing laws and regulations and the consequences for industries that do not distribute remuneration to laid-off workers during the Covid-19 pandemic. From the results of research reporting on the protection and remuneration of workers in the workplace, employers can provide a deferral of payment of wages if the employer cannot pay wages in accordance with the minimum wage regulations, through a requirement that requires negotiating with workers first.